Analysis of Improving Instructor Competence in Supporting the Achievement of Organizational Goals in the Industrial Development Job Training Center - Gaol, Porman Lumban; Hidayah, Puteri Sari; Prastika, Evelyn Tirza (KnE Social Sciences, 2025)
This research aims to determine strategies for increasing instructor competency in supporting organizational tasks at The Center for Job Training and Industrial Development (PPKPI). This research uses a descriptive qualitative approach. Data were collected through interviews with the Functional Instructor and the Head of the Jakarta PPKPI Competency Test Implementation and Training Unit. The results review the competency aspects of three sub-aspects from Edison, Anwar, and Komariyah (2020), namely knowledge, skills and attitude. In general, the competency aspect for improving instructor competency is good, but there are obstacles in realizing instructor competency to be able to achieve PPKPI’s tasks, namely carrying out job training in the fields of industry, commerce, and various vocational fields. To maximize the increase in instructor competency, it is recommended that the central government, especially the Ministry of Manpower of the Republic of Indonesia, routinely check instructor competency, especially in basic instructor training, and inspect practical training facilities to support the teaching and learning process.